VD_FINDINFO Jug / 2015 / 440 vom 26. Juni 2015 - VD Tribunal cantonal (2015)
ACQUITTEMENT, DÉPENS, TROMPERIE, ASTUCE, DOMMAGE MATÉRIEL, LÉSÉ, PARTIE CIVILE, DÉLAI DE RECOURS | 41 CO, 146 CP, 151 CP, 31 CP, 126 CPP (CH), 398 al. 2 CPP (CH), 399 al. 3 CPP (CH), 399 al. 4 CPP (CH), 423 al. 1 CPP (CH), 426 al. 2 CPP (CH), 428 al. 1 CPP (CH), 429 al. 1 let. a CPP (CH), 433 al. 1 CPP(CH), 433 al. 1 let. b CPP (CH)